Direct and green repairing of degraded LiCoO2 for reuse in lithium-ion batteries. Issue 8 (18th May 2022) - Wang, Junxiong; Zhang, Qi; Sheng, Jinzhi; Liang, Zheng; Ma, Jun; Chen, Yuanmao; Zhou, Guangmin; Cheng, Hui-Ming
Abstract: Traditional recycling processes of LiCoO2 rely on destructive decomposition, requiring high-temperature roasting or acid leaching to extract valuable Li and Co, which have significant environmental and economic concerns. Herein, a direct repairing method for degraded LiCoO2 using a LiCl–CH4 N2 O deep eutectic solvent (DES) was established. The DES is not used to dissolve LiCoO2 but directly serves as a carrier for the selective replenishment of lithium and cobalt. Replenishment of lithium restores LiCoO2 at different states of charge to a capacity of 130 mAh/g (at 0.1 C rate), while replenishing the cobalt increases the capacity retention rate of 90% after 100 cycles, which is comparable to pristine LiCoO2 . The DES is collected and reused multiple times with a high repair efficiency. This process reduces energy consumption by 37.1% and greenhouse gas emissions by 34.8% compared with the current production process of LiCoO2, demonstrating excellent environmental and economic viability. Abstract : This work provides a novel direct recycling method based on a sustainable lithium-containing deep eutectic solvent to regenerate degraded cathode materials of spent lithium-ion batteries.